Incidence of Corporate Income Tax (CIT) Exemption - Stanislas Agossadou (Universitas Airlangga, 2025)
Background: Tax incentives are widely used among developed and developing economies to promote and attract economic activity in their jurisdictions and can be introduced for a range of reasons (OECD, 2022). However,